IMPLEMENTASI GARAP MINIR DAN GARAP PATHET DALAM REBABAN GENDHING WIYANG - Ulung Alif Ghifari; Ananto Sabdo Aji (Keteg : Jurnal Pengetahuan, Pemikiran dan Kajian Tentang Bunyi, 2023)
This article entitled "Implementasi Garap Minir Dan Garap Pathet Dalam Rebaban Gending Wiyang" contains an analysis, description, and study of the Wiyang garap rebab. The main idea presented in this article is the application of minir céngkok in mérong and the implementation of pathet elaboration located on the second kenong inggah with the application of yo bapak rebab céngkok, enabling it to be elaborated using two pathet interpretations, namely sléndro sångå and sléndro manyurå. This research adopts a qualitative method. Data collection methods include literature review, direct or indirect observation, and interviews with relevant informants. In analyzing this article, several concepts are employed to underpin the author's ideas, namely garap, pathet, and mungguh. The research findings reveal the application of minir céngkok pasrèn in mérong based on the absence of vocal influence and pamijen elaboration, which mandates minir elaboration within it, rendering the minir elaboration in this facultative garap. The application of minir céngkok pasrèn in this yields garap several categories of minir elaboration, including whole minir, half minir, and three-quarters minir. In addition to minir elaboration, the implementation of pathet elaboration on inggah contributes to offering elaboration to make the composition more dynamic. This influences other elaborations, resulting in the perception of dynamism in the presentation of the Wiyang composition.